Shopping Motivation and Green Consumption: A Study about Green Buying Behavior of Pakistani Consumers - Imran Khan; Furrukh Bashir; Rashid Ahmad; Muhammad Ayub (iRASD Journal of Management)
Natural resource depletion, increase in global population, climate change, and unsustainable consumption behaviors have all wreaked havoc on the ecosystem around the world. Increased consumption of green products is among the most effective strategies in adoption of sustainable consumption. The purpose of current research is to investigates the effect of shopping motivation (utilitarian) antecedents’ impact on utilitarian motivation and also discussed the mediating effect of utilitarian motivation on the association between utilitarian motivation antecedents and intention to purchase green products. Online survey was used to collect the data and SEM(structural equation modeling) was used to analyze data. The antecedents of shopping motivation (utilitarian) influence the intention of consumer about green buying. Four out of five hypothesis were supported. The findings of current research enable practitioners and managers to formulate strategies for sustainable consumption.